Induksi Aquilaria malaccensis Menggunakan Kombinasi Fusarium oxysporum dan Asam Salisilat: Aquilaria malaccensis Induction Using a Combination of Fusarium oxysporum and Salicylic Acid - Rani, Diah Puspa; Jayuska, Afghani; Khotimah, Siti; Ardiningsih, Puji; Agus Wibowo, Muhammad (KOVALEN: Jurnal Riset Kimia, 2024)
Agarwood is a resin from agarwood-producing plants that are given certain stimulants, thus stimulating the tree's defense system. The defense system produced is in the form of a sweet-smelling phytoalexin compound, better known as agarwood. Stimulants that can stimulate the formation of Gaharu are biological inoculants and chemical inducers. In this research, the biological inoculant used the Fusarium oxysporum fungus, and the chemical inducer used salicylic acid. This research aims to determine the effectiveness of using a combination of Fusarium oxysporum and salicylic acid in producing agarwood resin. The combination treatment of Fusarium oxysporum and salicylic acid was carried out using the injection method on Aquilaria malaccensis tree branches, and induction was carried out for 3 months. This research shows that the TLC test results in all treatments contain aloes, which is proven by the discovery of phenolic and terpenoid compounds. The combination treatment produces a color change intensity that is not darker and has a broader color change zone compared to the single treatment. Therefore, it can be concluded that the combination of Fusarium oxysporum and salicylic acid is less effective in producing Gaharu than the single treatment.